Milk-Derived Extracellular Vesicles Suppress Inflammatory Cytokine Expression and Nuclear Factor-κB Activation in Lipopolysaccharide-Stimulated Macrophages - Susanne R. Ascanius; Maria S. Hansen; Marie S. Ostenfeld; Jan T. Rasmussen (Dairy, 2021)
In milk and milk products, small membrane-enclosed vesicles can be found, commonly termed extracellular vesicles (EVs). Milk-derived EVs have previously been suggested to have immunoregulatory properties, especially important for infants without a fully functioning immune system. In the present study, EV fractions were isolated from human milk, mature and colostrum bovine milk, and two dairy fractions, and successively surveyed for their immunomodulating effects on lipopolysaccharide (LPS)-stimulated macrophages (RAW264.7). RAW264.7 cell material and supernatant were evaluated by monitoring degradation of IκBα in the NF-κB pathway, and IL-6 and IL-1β cytokine production, using Western blotting and enzyme-linked immunosorbent assaying, respectively. The results revealed that preincubation with EVs derived from raw human and bovine milk lowered the LPS-activated response of the NF-κB pathway. Additionally, it was found that preincubation with EVs, from human and bovine milk as well as dairy whey or skim milk-derived fractions, decreased secretion of proinflammatory cytokines from LPS-activated RAW264.7 cells. The findings that milk-derived EVs can change the inflammatory response in macrophages support the notion that milk EVs have an important role in mother-to-infant communication and protection of a newborn.